The philosophy of the heart of Hryhoriy Skovoroda: a pedagogical view of the teachings of the outstanding Ukrainian thinker - Dovzhenko, T.; Nebytova , I. (New Collegium, 2022)
The article presents a pedagogical view of the philosophical teachings of the heart of Hryhoriy Skovoroda. The works of followers and biographers of are analyzed. H. Skovoroda, which outline the life of the philosopher. It is determined that the teachings of the heart are based on the idea of three worlds: the first – the macrocosm (Universe), the second – the microcosm (man), the third – the symbolic reality (Bible), which connects these two worlds and reflects them in itself. Quotes from the leading works of H. Skovoroda characterizing his philosophical doctrine of the heart. It is determined that the feelings and heart of H. Skovoroda became an instrument of knowledge, deepened the space of contemporary traditional science and brought his scientific thought to cosmic reality. Fragments of the biography of H. Skovoroda reflecting his philosophical views. It has been proved that in the history of Ukrainian culture the teachings of Hryhoriy Skovoroda became the starting point in the knowledge of the heart, combining religious and philosophical knowledge about it: the purified and enlightened human heart is the most important organ of metacognition (heart feeling).